From carbon markets to carbon morality: creative compounds as framing devices in online discourses on climate change mitigation - Koteyko, Nelya; Thelwall, Mike; Nerlich, Brigitte (Sage, 2010)
Lexical combinations of at least two roots around "carbon" as the hub, such as "carbon finance" or "carbon footprint," have recently become ubiquitous in English-speaking science, politics, and mass media. They are part of a new language evolving around the issue of climate change that can reveal how it is framed by various stakeholders. In this article, the authors study the role of these "carbon compounds" as tools of communication in different online discourses on climate change mitigation. By combining a quantitative analysis of their occurrences with a qualitative analysis of the contexts in which the compounds were used, the authors identify three clusters of compounds focused on finance, lifestyle, and attitudes and elucidate the communicative purposes to which they were put between the 1990s and the early 21st century. This approach may open up new ways of analyzing the framings of climate change mitigation initiatives in the public sphere.